Influence of Prosocial Motivation on Employee Creativity: The Moderating Role of Regulatory Focus and the Mediating Role of Knowledge Sharing - Tian, Xizhou; Peng, Xiqiang; Peng, Xiaoping (Frontiers in Psychology, 2021)
Stimulating and improving the creativity of employees are both theoretically and practically important. The relationship between prosocial motivation and creativity has gradually gained attention in recent years; however, in the context of controlling for intrinsic motivation, the influence process and results between the two are not yet clear. Based on the motivated information processing model, componential theory of creativity, and regulatory focus theory, this study analyzed the mediating role of knowledge sharing and the moderating role of regulatory focus in the relationship between prosocial motivation and the creativity of employees. For this, we used the PROCESS program and the bootstrap method to test the theoretical hypotheses. Consequently, a survey of 320 Chinese employees revealed that, under the condition of controlling for intrinsic motivation, the prosocial motivation of employees was positively related to creativity and partially mediated by knowledge sharing. Furthermore, regulatory focus negatively moderated the correlation between prosocial motivation and knowledge sharing. Specifically, we found that the higher the prevention focus was, the weaker the effect prosocial motivation had on knowledge sharing. Contrary to the hypothesis, promotion focus also played a negative moderating role. Thus, the results revealed the mechanism and boundary conditions of prosocial motivation on creativity. This study expands the research on prosocial motivation and provides guidance on how managers can enhance the creativity of their employees.